(3GdhdGjI Ydi eGd GdbGUQ aj GdbGfhf GdeUQj (B:s (3HMK eSJajV jJfGhd GdhdGjI hGdhUGjI (B/s - (3eMehO SYO GdOjf GdTQjas; (3CMeO Hc EHQGgje EHQGgjes; (3LGeYI aDGO GdChds (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb (B- (3LGeYI aDGO GdChd,s, 1941)
(3Gf fXGe GdhUGjg hGdhdGjg QZe JaGhJ WHjYJgeG hCNJdGa UjGZJgeG hcjajg GOGFgeG dhXjaJgeG hJHGjf eOi GdSdWGf GdPi GSHZ Ydi GdbGFejf HgeG jQJHWGf HChGUQ bhjg hjTJQcGf ai SeGJ eTJQcg JMce QHGWgeG ai GdbGfhf GdeUQi ageG jfJSHGf Gdi MXjQg GdGMhGd GdTNUjg ai eUQ hjNVYGf HMce gPG GdJcjja hGdJCUjd Gdi GdTQGFY GdOjfjg GdeNJdag GdJi JShO bhGYOgG GdehVhYjg hgeG GOGJGf aYGdJGf dMeGjg GdUZjQ hdgPG hLH GfbVGDgeG hRhGd SjWQJgeG Ydi GdUZjQ HRhGd GdGSHGH GdJi bGeG ef GLdgeG aJfbVi GdhdGjg hGdhUGjg YGOg HHdhZ GdUZjQ QTjOG(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI aDGO GdChd, cdjI GdMbhb, bSe GdTQjYI GdESdGejI (B1941.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajIs
Keywords: (3GdTQjYI GdESdGejIs; (3GdhdGjIs; (3SdWI GdChdjGAs; (3Gdhdjs; (3GdfXQjI GdYGeI ddZHfs; (3GdhUGjIs; (3GdhUjs; (3QSGFd LGeYjIs -- (3LGeYI aDGO GdChds -- (3TQjYI ESdGejIs